Immediate Results of Surgical Treatment of Gastric Cancer - Nurov Jamshid Rakhmatovich; Narzieva Dilnoza Fakhriddinovna (Research Parks Publishing LLC, 2021)
Analysis of the immediate results of surgical treatment of gastric cancer patients subjected to extended 55 gastrektomy withsplenektomy and 57 patients of control group, which has been implemented advanced gastrektomy without splenektomy. Advanced gastrektomy with splenektomy in surgical treatment of gastric cancer does not increase the number of postoperative complications and thenature of complications didnot differ from those after the extended gastrektomy with presegastriccanceration of the spleen.